2013
DOI: 10.3892/etm.2013.1012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of an ROC curve of the size of the antepartum foramen ovale in the prediction of puerperal atrial septal defect

Abstract: The aim of this study was to determine the diagnostic value of an ROC curve of the antepartum foramen ovale (AFO) size and the ratio of FO size to aorta (AO) size (FO/AO) for the prediction of puerperal atrial septal defect in different gestational weeks (DGWs). A total of 958 cases were divided into five groups according to number of gestational weeks. Comparisons of FO size, AO size and FO/AO were determined by variance analysis. The correlations between FO size, AO size and gestational age were determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…On the other hand, increased FO diameter has been associated with atrial septal defect (ASD) in postnatal life. Li et al, using ROC analysis, have reported that large FO diameters and FO/ Aorta ratios can be used to predict development of secundum ASD in the postnatal period [29]. Although there was no significant difference between the FO diameters in the two groups in our study, the DV-D and DV-a velocities were significantly increased in the study group, which is interpreted as an increased preload.…”
Section: Discussioncontrasting
confidence: 47%
“…On the other hand, increased FO diameter has been associated with atrial septal defect (ASD) in postnatal life. Li et al, using ROC analysis, have reported that large FO diameters and FO/ Aorta ratios can be used to predict development of secundum ASD in the postnatal period [29]. Although there was no significant difference between the FO diameters in the two groups in our study, the DV-D and DV-a velocities were significantly increased in the study group, which is interpreted as an increased preload.…”
Section: Discussioncontrasting
confidence: 47%